Isolation of endophytic fungi from Hiyung chili peppers of local South Kalimantan (Indonesia) varieties and in vitro tolerance to acidic environment - WITIYASTI IMANINGSIH; NURAENI EKOWATI; SALAMIAH SALAMIAH; NUNIEK INA RATNANINGTYAS; LOEKAS SOESANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Imaningsih W, Ekowati N, Salamiah, Ratnaningtyas NI, Soesanto L. 2023. Isolation of endophytic fungi from Hiyung chili peppers of local South Kalimantan (Indonesia) varieties and in vitro tolerance to acidic environment. Biodiversitas 24: 3844-3852. Hiyung chili (Capsicum frutescens L) is a local chili from Hyung Village, Tapin District, South Kalimantan Province, Indonesia which has the advantage of being cultivated with an agricultural system in swampland, with high production and is known to have high capsaicin also. This advantage is thought to be related to its symbiosis with endophytic microbes, especially fungi. The purpose of this study was to isolate and identify non-pathogenic endophytic fungi from Hiyung chili plants and determine their ability to tolerate acidic conditions in vitro. Results showed that a total of 41 endophytic isolates were isolated from different parts of chili plant. Of the 41 isolates four non-pathogenic endophytic fungi were isolated from leaf tissue. Based on morphological and molecular identification these four fungi were Pseudozyma hubeiensis DM3.1, Phoma sp. DT2.2P1, Letendraea sp. DM1.2 and Phoma sp. DT2.2P4. Four endophytic fungi showed different abilities in an in vitro preliminary study of acidic environmental stress tolerance. Only P. hubeiensis DM3.1 isolate had the daily diameter of colony not significantly different based on the Anova test (? :0.05, F: 1.092, P:0.372) both at pH 5, 4 and 3 and without pH treatment.